2020
DOI: 10.1177/1010428320957506
|View full text |Cite|
|
Sign up to set email alerts
|

Resistance to paclitaxel induces glycophenotype changes and mesenchymal-to-epithelial transition activation in the human prostate cancer cell line PC-3

Abstract: The development of the multidrug resistance phenotype is one of the major challenges faced in the treatment of cancer. The multidrug resistance phenotype is characterized by cross-resistance to drugs with different chemical structures and mechanisms of action. In this work, we hypothesized that the acquisition of resistance in cancer is accompanied by activation of the epithelial-to-mesenchymal transition process, where the tumor cell acquires a more mobile and invasive phenotype; a fundamental step in tumor p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 76 publications
1
8
0
Order By: Relevance
“…Thus, GnT-III is generally regarded as a key glycosyltransferase in N -glycan biosynthetic pathways ( 37 ). Previous studies have shown that the expression levels of GnT-III are decreased in several drug-resistant cell lines ( 38 , 39 ). Moreover, a knockdown of GnT-III has increased the resistance to 5-fluorouracil in human hepatocarcinoma cells ( 31 ).…”
mentioning
confidence: 97%
“…Thus, GnT-III is generally regarded as a key glycosyltransferase in N -glycan biosynthetic pathways ( 37 ). Previous studies have shown that the expression levels of GnT-III are decreased in several drug-resistant cell lines ( 38 , 39 ). Moreover, a knockdown of GnT-III has increased the resistance to 5-fluorouracil in human hepatocarcinoma cells ( 31 ).…”
mentioning
confidence: 97%
“…In respect to PTX resistance of prostate cancer cells, polymeric nanoparticles have been applied for targeted delivery of PTX [294]. Furthermore, activation of molecular mechanisms such as EMT stimulates PTX resistance [295]. LncRNA CCAT1 undergoes overexpression in PTX resistant-prostate cancer cells and prevents apoptosis.…”
Section: Role In Therapy Responsementioning
confidence: 99%
“…When it comes to N-linked glycans, however, there is more to the story. Many groups show an abundance of long, branched, and hypersialylated structures [30][31][32][33][34][35], while others report high mannose structures [36,37] or even both [38]. One particular study points to high mannose structures being prevalent in the primary tumor, while branched sialylated epitopes are found in metastatic foci [39].…”
mentioning
confidence: 99%
“…Recent studies have demonstrated that altered glycosylation of proteins that make up the glycocalyx may be recognized by immune cells, leading to induction of inhibitory immune processes, which subsequently drive tumor growth and metastasis [41]. Several studies developed by our research group demonstrated that Oand N-linked unusual glycan structures govern phenomena associated to the epithelial-mesenchymal transition (EMT) process, as well as the acquisition/maintenance of the multidrug resistance (MDR) phenotype [12,34,35,[42][43][44][45][46][47][48][49][50]. MDR phenotype and the acquisition of metastatic properties by cancer cells are known as the main obstacles to the treatment of different types of cancer [51].…”
mentioning
confidence: 99%
See 1 more Smart Citation